THE ROLE OF ORGANIZATIONAL IDENTIFICATION IN SHAPING SOCIAL EXCHANGE DYNAMICS WITHIN THE WORKPLACE: AN INTEGRATIVE PERSPECTIVE - Tavares, S. M. (Academy of Management 2025 Annual Meeting, 2025)
How employees relate to their organizations is a foundational question of organizational studies. Two main constructs have been widely employed in the literature to explain the psychological dynamics established between individuals and their employing organizations: social exchange (SE) (e.g., Cropanzano Anthony, Daniels, & Hall, 2017; Shore, Coyle-Shapiro, Chen, & Tetrick, 2009) and organizational identification (OI) (e.g., Ashforth & Mael, 1989; Ashforth, Harrison, & Corley, 2008; Bednar, Galvin, Ashforth, & Hafermalz, 2020). These theoretical perspectives have predominantly evolved in isolation. However, recent research has begun exploring their intersection and combined influence on employees’ attitudes and behaviors (e.g., Flynn, 2005; Hekman, Bigley, Steensma, & Hereford, 2009; Umphress, Bingham, & Mitchell, 2010; Simbula, Simona, & Avanzi. 2023; van Knippenberg, van Dick, & Tavares, 2007; Tavares, van Knippenberg, & van Dick, 2016). We propose an integrative model using SE and OI to enhance our understanding of how individuals think, feel and behave within organizational contexts. Social Exchange and Individual-Organization Mutual Influence Being an important societal mechanism for regulating social interactions (Blau, 1964), social exchange theory (SET) pervades organizational life, underpinning processes of individual-organization mutual influence and control. Based on reciprocity as “a necessary condition of exchange” (Blau, 1964, p. 89), SET emphasizes the motivational impact of resources obtained in the organizational context on individual cognitions, emotions, and behavior at work. As Blau (1964) posit, social exchange is an “intermediate case between pure calculation of extrinsic advantage and pure expression of intrinsic affection” (p.112). Examples of intrinsically rewarding organization-provided currencies are what Marcus and House (1973) called “expressive outcomes”: i.e., ones denoting social acceptance, approval, respect or support. Examples of extrinsically rewarding organization-provided currencies might be resources that, although social in their nature, may be instrumental to reach other outcomes. Advice, invitations, assistance, or compliance can fulfill this role (Blau, 1964, p.95). If individuals find organization social “exchange currencies" (Cole, Schaninger, & Harris, 2002) either intrinsically or extrinsically rewarding, this may prompt their discretionary and voluntary actions of reciprocation using exchange attitudinal currencies (such as satisfaction, commitment and trust), and behavioral currencies (e.g., absenteeism, turnover or innovation) regarding the organization and its stakeholders. Although Gouldner (1960) considers that reciprocity is “the basic glue underlying social exchange,” he also argues that “it is not unconditional” (p. 171). Hence, researchers have been signaling some factors that might shape the value attributed to reciprocity. Namely, cultural differences – e.g., individualism-collectivism (e.g., Rockstuhl et al., 2020; van Knippenberg, van Prooijen, & Sleebos, 2015) - and individual differences – e.g., employee exchange ideology (Eisenberger et al., 2001). But also, factors that influence the perceived value of the resource received. In fact, according to Gouldner (1960), “obligations of repayment are contingent upon the imputed value of the benefit received” (p. 171). The value assigned to any particular social currency and hence, the felt obligation to reciprocate, is dependent both on the characteristics and the situation of the donor – such as the resources of the donor, the motives imputed to the donor and the nature of the constraints that might have affected the donation - and on the characteristics and the situation of the recipient – such as the intensity of the recipient’s need of the benefit that is being bestowed at the time, the existence of alternative sources for supplying the needed resource (Gouldner, 1960, p. 164) and individual’s socio-emotional needs (esteem, affiliation, emotional support, and social approval; Armeli, Eisenberg, Fasolo, & Lynch, 1998). In the same vein, we contend that the value attributed to the organization's exchange currencies depends on how strongly the individual identifies with the organization they work for, which in turn determines the content of the exchange. Organizational Identification and Employee’s Behavior Differently from SET, OI’s framework (e.g., Ashforth & Mael, 1989) explains the relationship individuals establish with their organization grounded, not on the motivational potential of the resources exchanged, on individual’s self-interest, on the expectation of future retribution, or on the desire to maintain a positive self-image by avoiding the social stigma associated with the violation of the norm of reciprocity, but on individual’s self-definition. This involves either the actual, or the idealized, felt overlap between individuals’ identity and organizational identity, mission, ideology, values, strategies and customary ways of doing things (Ashforth & Mael, 1996). In other words, OI theorists explain how individuals relate to their employing organization based on their perception of oneness with the organization (Ashforth and Mael, 1989) and the centrality of their organizational membership to their sense of who they are (Ashforth et al., 2008). Research showed that OI shapes individual’s work attitudes - like job involvement, job satisfaction, and affective organizational commitment - and behaviors towards the organization - like in-role performance, extra-role performance, voice and creative behavior (cf. Lee, Park, & Koo, 2015 for a meta-analysis). In fact, individuals who identify more strongly with the organization they work for, more often display higher levels of perseverance, diligence, and effort on behalf of the organization. Instead of explaining these associations using the concept of felt obligation to reciprocate (a SET anchor), OI theoretical framework justifies that high identifiers act in accordance with organization interests and increase their efforts on organization’s behalf, due to four main reasons. One is that, for high identifiers, the effort on behalf of the organization is a behavioral expression of the self (Bartel & Dutton, 2001), assuring the maintenance of a sense of continuity, coherence and consistency (Tyler & Blader, 2001). Additionally, individuals’ behavior is a display of their identity enactment, being an indicator of the strength of their OI and, at the same time, helping them making sense of who they are and deriving meaning from their organizational membership (sensemaking role of the social performance of identity, cf. Ashforth et al., 2008). Furthermore, cooperation with the organization and its members can be a form of self-enhancement by contributing to the preservation of a positive organizational image and, consequently, to a positive social identity of the individual as a member of the organization (cf. Cialdini et al. 1976). Moreover, by acting in accordance with organization’s interests, these individuals positively reinforce the validation that others make of their subjective belonging, maintaining a favorable image as members of the organization, in an upward management strategy of their OI (Bartel & Dutton, 2001). Social Exchange and OI: An Integrative Approach Cole and colleagues (2002) argue that “the value assigned to any particular social currency will depend on the particular characteristics and needs of the individual” (p. 151). We propose that organizational identification qualifies the value attributed by employees to the organizational exchange currencies they receive, as well as the meanings individuals associate with these currencies, and the range of action strategies available to them to restore the balance in their relationship with the organization, thus conditioning the content of the social exchange. Therefore, we sustain that the level of the individual’s OI regulates the content of the SE (Tavares et al., 2016), essentially shaping the currencies individuals choose to employ in restoring equity in their SE relationship with the organization. We posit that OI delineates the array of SE currencies chosen by the individuals to rebalance their relationship with the organization, thus establishing a spectrum of behavioral strategies which each person considers appropriate for reciprocating the various resources received. There may be three mechanisms through which individual’s level of OI influences the content of SE: the meaning attributed to the resource received (relational, for high identifiers vs. instrumental, for low identifiers); the value imputed to the resource received (i.e., the centrality of the resource received for the individual); and the way individuals with different levels of OI build their role definition in the organization (role identity with a more broad vs. narrow definition of responsibilities; cf. Ashforth, 2001). We further explore how OI might regulate the content of SE by examining: a) a two-dimensional space of SE (Cropanzano et al., 2017), incorporating the hedonic value of the SE currency and the degree of action or inaction in the reciprocating response; b) social exchange with multiple foci in the organization (including the organization itself, supervisors, and coworkers) (cf. Cropanzano et al., 2017; Deng, Coyle-Shapiro, & Yang, 2018; Lavelle, Rupp, & Brockner, 2007); and c) the concept of negative reciprocity (Gouldner, 1960). We also address the challenges posed by new forms of work and the more diverse forms of employment that we face today.